Influence of Salt Concentration on the Properties of Sodium‐Based Electrolytes. Issue 4 (27th August 2018) - Geng, Chenxi; Buchholz, Daniel; Kim, Guk‐Tae; Carvalho, Diogo Vieira; Zhang, Huang; Chagas, Luciana Gomes; Passerini, Stefano
Abstract: Electrolytes based on organic carbonates are widely used for sodium‐ion batteries (SIBs) due to several advantages such as high ionic conductivity, wide liquidus range, and high electrochemical stability. In this work, this class of electrolyte is investigated focusing on two conductive salts, namely NaPF6 (sodium hexafluorophosphate) and NaTFSI (sodium bis(trifluoromethanesulfonyl)imide), using PC (propylene carbonate) as solvent. The investigation of different salt concentrations, from rather diluted to highly concentrated (i.e., 0.1, 1, and 3m ), extends from their glass transition temperature to viscosity, ionic conductivity, electrochemical stability window, and electrochemical stability toward Al. Raman spectroscopy discloses the salt–solvent coordination and its possible modification due to changes in temperature, proving that the viscosity played a major role in influencing ionic conductivity rather than ions and molecules' coordination. Finally, the electrochemical performance of half‐cells employing Na x Ni0.22 Co0.11 Mn0.66 O2 as the cathode material with the various electrolytes is also reported, and cells containing electrolyte with 1m salt concentration outperform the other in terms of delivered capacity and rate performance. Abstract : The ionic conductivity of high‐concentration sample strongly decreases with decreasing temperatures, differently than samples with lower concentrations. This is an effect of the dramatic change of viscosity by cooling down the samples, rather than related to the different coordination of electrolyte's molecules.